Candida glabrata chorioamnionitis in a twin pregnancy following in vitro fertilisation: a rare cause of septic miscarriage. Issue 2 (3rd February 2022) - Yusoff, Muhammad Ashraf; Wee, Ian Liang En; Sim, Jean Xiang Ying; Yang, Liying
Abstract : Candida glabrata chorioamnionitis is uncommon and associated with poor fetal outcomes. We present a case of C. glabrata chorioamnionitis of a dichorionic diamniotic pregnancy conceived by fresh embryo transfer. Despite antifungal therapy with amphotericin B, spontaneous miscarriage of both twins occurred. The mother otherwise recovered uneventfully. Our case highlights the high fetal mortality associated with C. glabrata chorioamnionitis and the challenges of antifungal treatment in pregnancy. We recommend a low threshold of suspicion for Candida infection in pregnancy, notably those involving transvaginal uterine instrumentation such as in vitro fertilisation.